Hubungan Merokok dan Kadar Leukosit pada Perokok Kronik - Sirih, Gabrielle E.; Engka, Joice N.; Marunduh, Sylvia M (e-Biomedik, 2017)
Abstract: Smoking is one of the leading causes of health problems in the world. The World Health Organization (WHO) shows that Indonesia is in third place with the largest number of smokers that reached 146.860.000 inhabitants. In North Sulawesi, almost one-third of the population aged ≥10 years are chronic active smokers with the average number of cigarettes smoked 10 cigarettes per day. WHO classifies smokers into mild, moderate, and severe smokers. Some studies found that cigarette smoking could affect the values of various blood parameters. This study was aimed to determine whether there was a relationship between chronic smoking and leukocyte levels in adult smokers. This was an analytical descriptive study with a cross-sectional design conducted on 30 students of Mechanical Engineering Faculty of Sam Ratulangi University Manado. Data were statistically analyzed with Kruskal-Wallis test on leukocyte, basophil, eosinophil, stem neutrophil, and monocyte meanwhile the One Way Anova on neutrophil segments, and lymphocytes. The Kruskal-Wallis test and the One Way Anova obtained all P values >0.05. Respondents had average leukocyte counts and normal white blood cell differential counts. Conclusion: There was no significant relationship between smoking andd leukocyte levels in chronic smokers.Keywords: chronic smokers, leukocyte level, white blood cell differential count Abstrak: Merokok merupakan salah satu penyebab masalah kesehatan terbanyak di dunia. World Health Organization (WHO) menyebutkan Indonesia berada pada urutan ketiga dengan jumlah perokok terbanyak yang mencapai 146.860.000 jiwa. Untuk daerah Sulawesi Utara, hampir sepertiga penduduk berusia ≥10 tahun merupakan perokok aktif kronik dengan rerata jumlah rokok yang dihisap 10 batang per hari. WHO menglasifikasikan perokok menjadi perokok ringan, sedang, dan berat. Beberapa penelitian melaporkan bahwa rokok dapat memengaruhi nilai dari berbagai parameter darah. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara merokok dan kadar leukosit pada perokok kronik. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang yang dilakukan pada 30 mahasiswa Jurusan Teknik Mesin Fakultas Teknik Universitas Sam Ratulangi Manado. Uji statistik Kruskal- Wallis dilakukan pada kadar leukosit, basofil, eosinofil, neutrofil batang, monosit sedangkan One Way Anova pada neutrofil segmen, dan limfosit. Baik pada uji Kruskal-Wallis maupun One Way Anova didapatkan semua nilai P >0,05. Responden memiliki rerata kadar leukosit dan hitung jenis leukosit yang normal. Simpulan: Tidak terdapat hubungan bermakna antara merokok dan kadar leukosit pada perokok kronikKata kunci: merokok kronik, kadar leukosit, hitung jenis leukosit